Factors affecting premenstruation syndrome in adolescent women Class XII IPA SMAN 1 Uluan Year 2022 - Novitarum, Lilis; Saragi, Helinida; Pakpahan, Rotua; manurung, Flora (International Journal on Health and Medical Sciences, 2023)
Premenstrual syndrome (PMS) is a collection of symptoms experienced by women before their menstrual period, which is 7-14 days before menstruation and will disappear at the beginning of menstruation, causing pain or swelling in the breasts, aches and pains, headaches, etc. Several factors that influence premenstrual syndrome are age at menarche, knowledge, body mass index and stress. The purpose of the study is to identify the factors that influence premenstrual syndrome (PMS) in on of IPA class XII of SMAN 1 Uluan 2022. The research method was descriptive research, the number of respondents are 57 people. The sampling technique is total sampling. The results obtained that some respondents experienced late menstruation at the age of >13 years, namely the majority were 26 people (45.6%) and the minority is at the age of early menarche <11 years, namely 8 people (14%). The results of data from 57 respondents who have good knowledge are 19 people (33.33%), 33 people (58%), and less are 5 people (8.5%). the results of 57 respondents, namely the majority had a normal body mass index (BMI) of 28 people (49%) and the minority had a body mass index (BMI) of obesity II as many as 2 people (3.5%). The results of the 57 respondents are the severe majority as many as 44 people (77.2%) and the mild minority as many as 13 people (22.8%). It is expected that on of IPA class XII of SMAN 1 Uluan 2022 can play an active role in reducing premenstrual syndrome problems, consuming healthy foods, avoiding foods that are taboo during menstruation. Regular exercise to reduce stress and deepen knowledge about premenstrual syndrome.